The Impact of practice Strategic Adaption on Economic Crisis Management Strategies under the Circumstances of War - Syrian Case from 2011 to 2018 - Al Zoubi, Orwa (The Arab Journal of Administration, 2019)
The present study aimed to identify the impact of practice strategic adaption on economic crisis management strategies under the circumstances of the Syrian war, identifying the procedures, which the ministries took to address the present economic crisis and determine the obstacles, which faced the ministries in managing the crisis. The study used a descriptive analytical method, where (172) questionnaires distributed to respondents who occupied upper and middle administrative positions at six governmental ministries and institutions in Syria. The study revealed a statistically significant impact of practice strategic adaption on economic crisis management strategies, and that some procedures have been taken such as: Prevent the importation of many products that consume foreign exchange reserves such as new cars and luxury products, Reliance on private sector companies to import materials that the Syrian government is not allowed to import due to economic sanctions and opening a credit line with Iran worth one billion dollars to provide oil derivatives and other goods. The study recommended forming a committee of senior experts from the six ministries to develop adaptive strategies for managing the crisis and review them periodically every 6 months and reducing the domestic demand of foreign exchange through control of imports, seizure of smuggling operations, and speculation.